Pilot Study on the Genetic Background of an Active Matrix Metalloproteinase‐8 Test in Finnish Adolescents. Issue 5 (1st May 2017) - Heikkinen, Anna Maria; Raivisto, Teija; Kettunen, Kaisa; Kovanen, Leena; Haukka, Jari; Pakbaznejad Esmaeili, Elmira; Elg, Jessica; Gieselmann, Dirk‐Rolf; Rathnayake, Nilminie; Ruokonen, Hellevi; Tervahartiala, Taina; Sorsa, Timo
Abstract : Background: In periodontitis, genetics and smoking play important roles in host immune system response. The aim of this study is to determine whether the genetic background of initial periodontitis and caries could be detected using an active matrix metalloproteinase (aMMP)‐8 chairside test in Finnish adolescents. Methods: Forty‐seven participants gave approval for analysis of both oral fluid collection and DNA. An aMMP‐8 chairside test was performed on participants (adolescents aged 15 to 17 years), and full‐mouth clinical parameters of oral health were assessed including periodontal, oral mucosal, and caries status in Eastern Finland from 2014 to 2015. DNA was extracted from oral fluid samples and genotyped for 71 polymorphisms in 29 candidate genes for periodontitis. Results were analyzed using a logistic regression model. P values were corrected for multiple testing using false discovery rate (<0.05). Results: aMMP‐8 chairside test positivity and three or more ≥4 mm pockets were associated with vitamin D receptor ( VDR ) (rs2228570, P = 0.002, q = 0.04) and MMP3 (rs520540, rs639752, rs679620, P = 0.0009, 0.003, 0.003, q = 0.04, respectively). None of the other single‐nucleotide polymorphisms studied showed a significant association with the aMMP‐8 chairside test and at least one caries lesion positivity. Conclusion: Genetic polymorphisms of MMP3 and VDR are linked to initial periodontitis in Finnish adolescents, and the aMMP‐8 chairside test can eventually detect initial periodontitis in young patients with predisposing genetic background.